Activity of neem tree (Azadirachta indica) leaves aqueous extract on Spodoptera frugiperda - Prates, Hélio Teixeira; Viana, Paulo Afonso; Waquil, José Magid (Pesquisa Agropecuaria Brasileira, 2003)
The fall armyworm (Spodoptera frugiperda (J. E. Smith)) has been controlled with synthetic insecticides bringing risk to the environment. Neem (Azadirachta indica A. Juss) is reported to be a natural alternative to synthetic insecticides against many insect species. The objective of this work was to evaluate the activity of neem leaves aqueous extract on fall armyworm, in laboratory. Bioassays carried out using artificial feed with various extract concentrations, and chlorpyrifos as control, indicated, 15 days after larvae infestation, similar efficiency in concentrations from 3.60 to 10.00 mg mL-1. Probit analysis showed LC50 = 2.67 mg mL-1. Hence, aqueous extract from neem leaves are active against fall armyworm.